2002
DOI: 10.1002/art.10673
|View full text |Cite
|
Sign up to set email alerts
|

Identity of the RNase MRP– and RNase P–associated Th/To autoantigen

Abstract: Objective. To characterize the molecular identity of the Th/To autoantigen, which is targeted by autoantibodies in scleroderma and which is associated with the human RNase MRP and RNase P ribonucleoprotein complexes.Methods. Proteins immunoprecipitated by antiTh/To؉ patient antisera from biotinylated total HeLa cell extracts were analyzed by immunoblotting. The association of autoantigenic proteins with the RNase MRP complex was analyzed by reconstitution experiments and ultraviolet crosslinking. The reactivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
44
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 27 publications
2
44
0
2
Order By: Relevance
“…For most of these proteins, coimmunoprecipitation experiments demonstrated that they are, indeed, associated with both RNase MRP RNA and RNase P RNA in human cell lines (Pluk et al 1999;van Eenennaam et al 2002). Moreover, all 10 proteins copurified with catalytically active RNase P, suggesting that they are part of the core structure of the holoenzyme.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…For most of these proteins, coimmunoprecipitation experiments demonstrated that they are, indeed, associated with both RNase MRP RNA and RNase P RNA in human cell lines (Pluk et al 1999;van Eenennaam et al 2002). Moreover, all 10 proteins copurified with catalytically active RNase P, suggesting that they are part of the core structure of the holoenzyme.…”
Section: Discussionmentioning
confidence: 98%
“…Surprisingly, Rpp25 and Rpp20 were not detected at all in 60-80S fractions, even though they have been demonstrated to be stably associated with RNase MRP (van Eenennaam et al 2002). Rpp25 and Rpp20 are evolutionarily related proteins, both belonging to the Alba superfamily (Aravind et al 2003), which directly bind to each other (Welting et al 2004) and most likely bind as a heterodimer to the P3 domain of RNase MRP RNA (Pluk et al 1999;van Eenennaam et al 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Later, it has been shown that this antibody directs against subunits of mitochondrial RNA processing and ribonuclease P complexes 32 . Of at least 6 subunits consisting of these complexes, a 120-kDa protein contains the major autoantibody epitope Anti-PM-Scl antibody produces a homogenous nucleolar pattern, and is rarely found in non-Caucasian patients 36 .…”
Section: Anti-th/to Antibodymentioning
confidence: 99%
“…Components of the ribonuclease MRP and ribonuclease P complexes are targeted by anti-Th/To antibodies [59]. They are present in a minority of patients with SSc (2-5 %) and seem to characterize a novel subset of patients with limited skin involvement (similar to ACA) but high risk for severe organ involvement and worse prognosis [17,42,60].…”
Section: Anti-th/to Antibodiesmentioning
confidence: 99%